Covert affairs. Season three [videorecording (DVD)] - Kroeker, Allan; Perabo, Piper; Gorham, Christopher, 1974-; Matchett, Kari (Universal Studios Home Entertainment, 2013)
One month before her CIA training is over, agent Annie Walker is summoned for active duty in one of the agency's most secretive branches, but unknown to her, Annie is being used as bait by her bosses to get someone or something from her past.